A novel automated behavioral test battery assessing cognitive rigidity in two genetic mouse models of autism - Puścian, Alicja; Łęski, Szymon; Górkiewicz, Tomasz; Meyza, Ksenia; Lipp, Hans-Peter; Knapska, Ewelina (Frontiers in Behavioral Neuroscience, 2014)
Repetitive behaviors are a key feature of many pervasive developmental disorders, such as autism. As a heterogeneous group of symptoms, repetitive behaviors are conceptualized into two main subgroups: sensory/motor (lower-order) and cognitive rigidity (higher-order). Although lower-order repetitive behaviors are measured in mouse models in several paradigms, so far there have been no high-throughput tests directly measuring cognitive rigidity. We describe a novel approach for monitoring repetitive behaviors during reversal learning in mice in the automated IntelliCage system. During the reward-motivated place preference reversal learning, designed to assess cognitive abilities of mice, visits to the previously rewarded places were recorded to measure cognitive flexibility. Thereafter, emotional flexibility was assessed by measuring conditioned fear extinction. Additionally, to look for neuronal correlates of cognitive impairments, we measured CA3-CA1 hippocampal long term potentiation (LTP). To standardize the designed tests we used C57BL/6 and BALB/c mice, representing two genetic backgrounds, for induction of autism by prenatal exposure to the sodium valproate. We found impairments of place learning related to perseveration and no LTP impairments in C57BL/6 valproate-treated mice. In contrast, BALB/c valproate-treated mice displayed severe deficits of place learning not associated with perseverative behaviors and accompanied by hippocampal LTP impairments. Alterations of cognitive flexibility observed in C57BL/6 valproate-treated mice were related to neither restricted exploration pattern nor to emotional flexibility. Altogether, we showed that the designed tests of cognitive performance and perseverative behaviors are efficient and highly replicable. Moreover, the results suggest that genetic background is crucial for the behavioral effects of prenatal valproate treatment.